Implications for cost and access of site-of-service referrals for ancillary medical services in a US Medicaid population: analysis of claims data from Maryland, USA - Maqbool Dada; Simrita Singh; Kelsey J Rydland; Chester Chambers; Vishal Mundlye; Edward Kumian; Kayode Ayodele Williams (BMJ Open)
Objectives Through analysis of claims and payment data, we quantified several implications of shifting ancillary healthcare services from regulated, more expensive to unregulated, less expensive sites. We also quantified the implications of this shift on access to services, with a focus on differences in access between rural and urban patients for a Medicaid (disadvantaged) population in Maryland, USA.Design Using a dataset of all Medicaid claims records for 1 year, we identified and extracted all bundles of regulated and unregulated ancillary services. Geospatial computing was used to approximate transportation costs required to access services. Including transportation enabled us to estimate net savings of any added transportation costs. We used location-allocation optimisation models to find the optimal sites to minimise net costs.Setting Coverage area included Medicaid patients throughout the state of Maryland.Participants All rural and urban members of this Medicaid cohort.Primary and secondary outcome measures Change in payer costs and member travel times on shifting ancillary bundles from regulated to unregulated sites.Results Procedure cost and travel time differentials between regulated and unregulated sites strongly correlated with the percentage of procedures referred to regulated sites. Shifting regulated bundles to unregulated sites, while imposing the constraint of no increase in travel time, reduced expenditures by 15.9%. This figure exceeded 30% if no limit was placed on travel-time increases.Conclusion With reasonable constraints on allowable travel time increases, shifting ancillary service bundles from regulated to unregulated sites can benefit both patients and payers in terms of cost and access.